China's country image in the eyes of international students from central Asian countries - Xueyan Zhao; Xuqun You; Shanyan Lin (Frontiers in Psychology, 2022)
This study aimed to investigate the conceptualization and measurement of China's country image (CI) as well as its effects on the economic image, product image, national image and residence intention of individuals. A total of 297 international students from central Asia were recruited to complete an online survey. The confirmatory factor analysis of CI scale showed that CI is a multidimensional construct consisting of a cognitive component (further be divided into government image, international image, and social image) and an affective component. Participants' ratings on China's CIs before and after coming to China were compared by using a repeated-measures ANOVA and paired sample t-tests, and the results showed a significant difference in government image and international image but no significant difference in social image. The regression analysis showed that CI significantly predicted the economic image, product image, national image and individual's residence intention. This study demonstrated a theoretical insight of CI research and could potentially contribute to optimizing strategies to improve the country reputation.